Highly efficient adsorption desalination employing protonated-amino-functionalized MOFs - Han, Bo (2022)
The MOFs (metal organic frameworks) namely MIL-101 (Cr), MIL-125 (Ti) and UiO-66 (Zr) are found suitable for desalination and cooling applications. To improve both cooling and desalination performances, these MOFs were embedded with amino (–NH2) functional groups. For further improvement of water adsorption capacity and rates, the amino-functionalized MOFs can be protonated with hydrochloric acid (HCl). This article at first deals with the synthesis and characterization of protonated-amino-functionalized (NH3+Cl−) MIL-101 (Cr), MIL-125 (Ti) and UiO-66 (Zr) MOFs. Secondly, under adsorption and desorption conditions, the H2O loadings on these adsorbents are evaluated from transient to steady states. The experimental results show that the protonation (NH3+Cl−) based MIL-101 (Cr), MIL-125 (Ti) and UiO-66 (Zr) MOFs show the greater water distribution of 0.35, 0.31 and 0.4 kg/kg of MOFs. According to experimental results (heat exchanger performance, adsorption isotherms and kinetics data), the performance criteria such as specific cooling capacity (SCP), daily water production (SDWP) and coefficient of performance (COP) are evaluated for various desorption temperature (60 to 80°C) and cycle time (100 to 1000 s). The simulation results show a remarkable improvement in water production i.e., SDWP > 50 m3 desalinated water/t of adsorbents/day for protonated UiO-66 (Zr) MOFs. Additionally, the SCP improves from 0.006 to 0.72 kW/kg of MOFs.